The Charged Linker Modulates the Conformations and Molecular Interactions of Hsp90 - López, Abraham (Chembiochem, 2020)
The molecular chaperone Hsp90 supports the functional activity of specific substrate proteins (clients). For client processing, the Hsp90 dimer undergoes a series of ATP‐driven conformational rearrangements. Flexible linkers connecting the three domains of Hsp90 are crucial to enable dynamic arrangements. The long charged linker connecting the N‐terminal (NTD) and middle (MD) domains exhibits additional functions in vitro and in vivo. The structural basis for these functions remains unclear. Here, we characterize the conformation and dynamics of the linker and NTD−MD domain interactions by NMR spectroscopy. Our results reveal two regions in the linker that are dynamic and exhibit secondary structure conformation. We show that these regions mediate transient interactions with strand β8 of the NTD. As a consequence, this strand detaches and exposes a hydrophobic surface patch, which enables binding to the p53 client. We propose that the charged linker plays an important regulatory role by coupling the Hsp90 NTD−MD arrangement with the accessibility of a client binding site on the NTD.